Comportamento da acidentalidade no processo de implementação de soluções tecnológicas na gestão da segurança viária no Espírito Santo - Santos, Ricardo Alves (2023)
Introduction: Reports from the World Health Organization (WHO) on traffic safety highlight that the occurrence of traffic accidents is the eighth cause of death in the world, reaching a total of one and a half million deaths worldwide, causing approximately 50 millions of wounded. Changing this ratio has required round-the-clock strategizing and planning. With technological advances, it is essential to make inspection dynamic in different critical points of accident, with planning and management, seeking to achieve a change in behavior in these places, intensifying the ostensive presence in the correct period. The problem is that planning is sometimes based on empiricism, built in an unsystematic way, without statistical parameters. Acting with a focus on prevention and immediate intervention in serious accidents implies directing the necessary resources, human and material, to the road sections with the highest incidence of these events, based on the improved analysis of statistical data. With the lack of planning, the results can be compromised, through which, through an Operation called Praevenire, an attempt was made to verify how much the use of technological tools could impact on the reduction of accidents on the federal highways of the State of Espírito Santo . The main objective is to characterize the implementation of technological solutions in the management of road safety in Espírito Santo through a statistical cross-sectional study with a quantitative approach. In theoretical terms, the research was supported by the search for tools for the analysis of traffic accidents using a geographic information system, providing managerial control. As for the methods and procedures, a quantitative and qualitative approach was used, based on a survey of accidentalities, configuring the research as bibliographical, documental and applied. Data collection was carried out using official accident records available in the Open Data of the Federal Highway Police. Through this survey, panels were developed that seek to provide precise elements to enable planning at the place of accidents, at the time of greatest occurrence. The results showed that with the use of tools that help in the planning and management of activities, it was possible to achieve results that effectively reduced accidents on federal highways in Espírito Santo. From the results, as a technical product, dashboards will be implemented that will aim to bring together management tools that will provide planning using official, technical and impersonal data, with the purpose of reducing serious accident rates. This tool will provide the manager with access to precise accident data, grouped together in order to enable technical planning.